Effect of testing protocol and within-pen prevalence on the detection of Mycoplasma hyopneumoniae DNA in oral fluid samples - Silva, Ana Paula S. Poeta; Storino, Gabriel Y. [UNESP]; Ferreyra, Franco S. Matias; Zhang, Min; Miller, Jessica M.; Harmon, Karen M.; Gauger, Phillip C.; Witbeck, Wendy; Doolittle, Kent; Zimmerman, Silvia; Wang, Chong; Derscheid, Rachel J.; et al. (Elsevier, 2022)
Combinations of 2 nucleic acid extractions and 3 Mycoplasma hyopneumoniae (MHP) PCRs (namely Protocol 1, 2, 3, and 4) were compared in terms of the probability of detecting DNA in pen-based oral fluid samples as a function of within-pen MHP prevalence. Oral fluid samples were created by randomly assigning 39 7-week old pigs to one of 5 pens, i.e., negative control pen (3 pigs) and 4 pens of 9 pigs each that differed in the proportion of MHP-inoculated pigs (1, 3, 6, or 9). Deep tracheal swabs were collected twice weekly to establish individual pig MHP infection status and derive within-pen prevalence estimation. On DPI 3, tracheal swabs from 15 of 19 inoculated pigs were MHP DNA positive. Oral fluids (n = 320) were collected daily from − 4 to 59 days post inoculation (DPI). Using a piecewise exponential model to account for within-pen transmission dynamics followed by a mixed-effect logistic regression, the probability of detecting MHP DNA in oral fluids was positively associated with within-pen prevalence (P < 0.0001) and differed among test protocols. MHP DNA was detected in 173 oral fluid samples with Protocol 3 versus 148, 134, and 101 with Protocols 4, 2, and 1, respectively. At 100% within-pen prevalence, the probability of detecting MHP DNA in oral fluids was highest using Protocol 3 (95.7%), followed by Protocols 4 (70.1%), 2 (60.1%), and 1 (34.0%). The fact that PCR protocols performed differently suggests that further improvements in extraction methods and MHP PCRs are possible. In the field, the dynamics of MHP infections should be taken into account if using oral fluid samples in surveillance.
Keywords: Cutoff; DNA; Mycoplasma hyopneumoniae; Oral fluid; PCR; Probability of detection; Tracheal swab